International management : strategic opportunities and cultural challenges - Sweeney, Paul D., 1955- (Routledge, 2015)
As the economies of many countries become more interrelated, international managers are facing huge challenges and unique opportunities associated with their roles. Now in its fifth edition, Sweeney and McFarlin's International Management embodies a balanced and integrated approach to the subject, emphasizing the strategic opportunities available to firms on a global playing field, as well as exploring the challenges of managing an international workforce. Integrating theory and practice across all chapter topics, this book helps students to learn, grasp, and apply the underlying principles of successful international management: Understanding the broad context of international business, including the critical trends impacting international management, the legal and political forces driving international business, and the ethical and cultural dilemmas that can arise Mastering the essential elements of effective interaction in the international arena, from cross-cultural understanding and communication to cross-border negotiation Recognizing and taking advantage of strategic opportunities, such as entering and operating in foreign markets Building and leading effective international teams, including€personal and behavioral motivation, as well as taking an international perspective on the hiring, training, and development of employees These principles are emphasized in the text with current examples and practical applications, establishing a foundation for students to apply their understanding in the current global business environment. With a companion website featuring an instructor?s manual, powerpoint slides, and a testbank, International Management, 5e is a superb resource for instructors and students of international management.- Resumé vydavatel
Keywords: nadnárodní společnosti; management; international business enterprises; elektronické knihy; učebnice; electronic books; textbooks